Measures of Kindergarten Spelling and Their Relations to Later Spelling Performance. (2nd September 2016) - Treiman, Rebecca; Kessler, Brett; Pollo, Tatiana Cury; Byrne, Brian; Olson, Richard K.
ABSTRACT: Learning the orthographic forms of words is important for both spelling and reading. To determine whether some methods of scoring children's early spellings predict later spelling performance better than do other methods, we analyzed data from 374 U.S. and Australian children who took a 10-word spelling test at the end of kindergarten ( M age = 6 years 2 months) and a standardized spelling test approximately 2 years later. Surprisingly, scoring methods that took account of phonological plausibility did not outperform methods that were based only on orthographic correctness. The scoring method that is most widely used in research with young children, which allots a certain number of points to each word and which considers both orthographic and phonological plausibility, did not rise to the top as a predictor. Prediction of Grade 2 spelling performance was improved to a small extent by considering children's tendency to reverse letters in kindergarten.